Cash flows discounted using a model-free SDF extracted under a yield curve prior - A. Ronald Gallant; George Eugene Tauchen (Journal of Risk and Financial Management, 2021)
We developed a model-free Bayesian extraction procedure for the stochastic discount factor under a yield curve prior. Previous methods in the literature directly or indirectly use some particular parametric asset-pricing models such as with long-run risks or habits as the prior. Here, in contrast, we used no such model, but rather, we adopted a prior that enforces external information about the historically very low levels of U.S. short- and long-term interest rates. For clarity and simplicity, our data were annual time series. We used the extracted stochastic discount factor to determine the stripped cash flow risk premiums on a panel of industrial profits and consumption. Interestingly, the results align very closely with recent limited information (bounded rationality) models of the term structure of equity risk premiums, although nowhere did we use any theory on the discount factor other than its implied moment restrictions.
Keywords: C32; C36; E27; 330; yield curve; Bayesian; bounded rationality; cash flows; discounting; moment functions; stochastic discount factor